Queueing theory based vehicular traffic management system through Jackson Network Model and Optimization - Suma, Tanjim Mushtari; Mahbub, Md. Shazid Bin; Uddin, Sk Mahtab; Siam, Md. Bony Amin Khan (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.